High-voltage pixel detectors in commercial CMOS technologies for ATLAS, CLIC and Mu3e experiments - Peric, Ivan; Fischer, Peter; Kreidl, Christian; Nguyen, Hong Hanh; Augustin, Heiko; Berger, Niklaus; Kiehn, Moritz; Perrevoort, Ann-Kathrin; Schöning, André; Wiedner, Dirk; Feigl, Simon; Heim, Timon; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
High-voltage particle detectors in commercial CMOS technologies are a detector family that allows implementation of low-cost, thin and radiation-tolerant detectors with a high time resolution. In the R/D phase of the development, a radiation tolerance of 1015neq/cm2, nearly 100% detection efficiency and a spatial resolution of about 3μm were demonstrated. Since 2011 the HV detectors have first applications: the technology is presently the main option for the pixel detector of the planned Mu3e experiment at PSI (Switzerland). Several prototype sensors have been designed in a standard 180nm HV CMOS process and successfully tested. Thanks to its high radiation tolerance, the HV detectors are also seen at CERN as a promising alternative to the standard options for ATLAS upgrade and CLIC. In order to test the concept, within ATLAS upgrade R/D, we are currently exploring an active pixel detector demonstrator HV2FEI4; also implemented in the 180nm HV process.
Gesehen am 03.01.2022